Women's Representation as Members of the General Election Supervisory Board - Mutiarahmanika, Fakhrana; Pakasi, Diana Teresa (International Journal Labs, 2023)
This study aims to determine the challenges of women's representation as Bawaslu members and the resulting impact of the low percentage of women in Bawaslu. Many previous studies have examined the challenges and obstacles in realizing women's representation in politics, especially in the context of elections, but there is still a lack of studies on women's representation in the Election Supervisory Body (Bawaslu). This research was conducted using Anne Phillips' theory of Political Representation. This descriptive research is a literature study involving books, journals, research, and websites as data. The results show that the current challenges to women's representation as members of the Indonesian Bawaslu are the lack of natural resources for women, a gender-neutral selection process, and a lack of knowledge about elections. As a result, women become politically illiterate, especially with regard to elections, gender equality in the Bawaslu commissioners does not materialize.